Prevalence and antimicrobial resistance of vibrio spp. In retail shrimps in Vietnam - Vu Thi Thu Tra (2018)
© 2016 Schlütersche. The aim of the study was to investigate the prevalence the antimicrobial resistance patterns of Vibrio (V.) spp. isolated from retail shrimp in Hanoi Vietnam. A total of 202 shrimp samples were collected from retail markets located in ten urban districts of Hanoi. Among those 201 (99.5%) samples were positive for Vibrio spp. The most common species detected was V. parahaemolyticus (96.5%) followed by V. alginolyticus (56.4%) V. cholerae (2%) V. vulnificus (1.5%). Multiple Vibrio spp. were found in 114 (56.4%) samples. None of the V. parahaemolyticus isolates carried the virulence-associated tdh (thermostable direct haemolysin) trh (tdh-related haemolysin) genes. In total 195 V. parahaemolyticus isolates four V. cholerae isolates three V. vulnificus isolates were tested for resistance to eight antimicrobial agents. V. parahaemolyticus isolates showed high rates of resistance against ampicillin (87.2%) while a moderate rate was observed for sulfamethoxazole/trimethoprim (18.5%) intermediate resistance towards tetracycline (24.6%). Low resistance rates (0.5%) were recorded against both ciprofloxacin cefalothin. Only one V. cholerae isolate with resistance to ampicillin two V. cholerae isolates with resistance to sulfamethoxazole/trimethoprim were found. All V. vulnificus isolates were susceptible to the eight antimicrobial agents tested. However the number of V. vulnificus V. cholerae was small. Multi-resistant isolates were found in V. parahaemolyticus with a low frequency (16.9%). The results of this study revealed the ubiquitous nature of Vibrio spp. in shrimp at retail. To reduce the potential risk of Vibrio infections due to handling or consumption of undercooked seafood good manufacturing practice as well as safe handling processing should be encouraged.